Experimental and numerical investigation of heat transfer in CNT nanofluids - Rashmi, Walvekar; Siddiqui, Mohammad Khalid; Ismail, Ahmad Faris; Saidur, R.; Rashid, A. K. (Taylor & Francis, 2015)
Nanofluids with their enhanced thermal conductivity are believed to be a promising coolant in heat transfer applications. In this study, carbon nanotube (CNT) nanofluids of 0.01 wt%, stabilised by 1.0 wt% gum arabic were used as a cooling liquid in a concentric tube laminar flow heat exchanger. The flow rate of cold fluid varied from 10 to 50 g/s. Both experimental and numerical simulations were carried out to determine the heat transfer enhancement using CNT nanofluids. Computational fluid dynamics (CFD) simulations were carried out using Fluent v 6.3 by assuming single-phase approximation. Thermal conductivity, density and rheology of the nanofluid were also measured as a function of temperature. The results showed thermal conductivity enhancement from 4% to 125% and nearly 70% enhancement in heat transfer with increase in flow rate. Numerical results exhibited good agreement with the experimental results with a deviation of +-3:0%. CNT nanofluids at 0.01 wt% CNTs showed Newtonian behaviour with no significant increase in the density.